Improving Vocabulary Mastery with English Kids' Songs: A Study in Primary Education - Kholid, M. Fikri; Rini, Yulan Puspita; Winasari, Bening Tyas (Cipta Pustaka Nusantara, 2024)
This study explores the impact of English kids' songs on vocabulary mastery among fifth-grade students at SD Islam Assalam. Utilizing a quasi-experimental design, the study compares an experimental group, taught vocabulary through English kids' songs, with a control group that followed traditional textbook-based instruction. Both groups completed pre- and post-tests to measure vocabulary acquisition. Results indicated a significant improvement in the experimental group, with an average post-test score increase of 42.9%, compared to a 10.3% improvement in the control group. The experimental group showed gains across different vocabulary categories—nouns, verbs, and adjectives—suggesting that songs enhance vocabulary retention through repetition, rhythm, and emotional engagement. These findings support the use of songs as a viable instructional tool for vocabulary learning, particularly for young learners who benefit from multisensory and associative learning techniques. While promising, the study's limitations, such as a small sample size and short intervention period, suggest the need for further research to validate these findings across diverse educational settings. Future studies should consider expanding sample sizes, extending the duration, and comparing song-based learning with other multimedia approaches. This research offers valuable insights for educators and curriculum developers, underscoring the potential of integrating songs to make vocabulary learning both engaging and effective.